1991
DOI: 10.1016/0014-5793(91)80051-4
|View full text |Cite
|
Sign up to set email alerts
|

Daily amylin replacement reverses hepatic glycogen depletion in insulin‐treated streptozotocin diabetic rats

Abstract: In strcptozotocin-diabetic rats treated with insulin replacement, liver glycogen is some 35% depleted. Five consecutive daily subcutaneous injections with amyiin dose-dependently restored liver glycogen to normal levels. Significant mcreases over insulin-only therapy occurred with amylin doses of 10.30 and 100 ,ug/day, representing amylin: insulin ratios of 0.22.0.75 and 2.79.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

1991
1991
2017
2017

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(8 citation statements)
references
References 25 publications
0
8
0
Order By: Relevance
“…Native amylin has been reported to normalize hepatic glycogen stores in insulin-treated streptozocin diabetic rats [4], an effect presumed to be secondary to increased hepatic lactate supply from muscle [27]. However a suppresion of glucagon levels by normalized amylin levels leading to increased liver glycogen content remains a possibility.…”
Section: Discussionmentioning
confidence: 99%
“…Native amylin has been reported to normalize hepatic glycogen stores in insulin-treated streptozocin diabetic rats [4], an effect presumed to be secondary to increased hepatic lactate supply from muscle [27]. However a suppresion of glucagon levels by normalized amylin levels leading to increased liver glycogen content remains a possibility.…”
Section: Discussionmentioning
confidence: 99%
“…Tissue-specific CGRP levels would be a more accurate measure of physiological effect of CGRP, as plasma CGRP levels might be due to spillover (22). Pre-clinical studies showed that increased pancreatic storage of CGRP results in insulin resistance (43,74). However, studies using radioimmunoassay, radio-receptor assay, and immunoradiometric assay demonstrated a strong correlation between the levels of CGRP in plasma and tissue extracts of rats and humans (22,24).…”
Section: Discussionmentioning
confidence: 99%
“…The role of CGRP in glucose homeostasis is diverse and complex, given its presence in the central, peripheral, and enteric nervous system, as well as the pancreas (23,27). Studies conducted predominantly in obese and type 2 diabetic rats have shown that infusion of pharmacological doses of CGRP induces insulin resistance and decreases peripheral glucose clearance (15,24,(42)(43)(44)(45)(46)(47). Whether this holds true in patients with CHAP is not known.…”
Section: Discussionmentioning
confidence: 99%
“…It has previously been postulated that amylin deficiency could aggravate hypoglycaemia in insulin-treated patientsp,35] The concurrent administration of amylin with insulin elicited a dosedependent response in amylin-deficient diabetic rats with restoration of normal hepatic glycogen levels, a finding that was interpreted as consistent with amylin-mediated stimulation of the indirect Cori cycle. [132] Amylin also enhances the stimulation of hepatic glucose production by glucagon and the recovery from insulin-induced hypoglycaemia in normal rats) 68] A recent study of acute administration of an amylin analogue has generated preliminary evidence for a beneficial effect of parenterally administered amylin in insulin-treated human patients with IDDM. [133] In amylin-treated patients, postprandial hyperglycaemic excursions were decreased compared with matched controls.…”
Section: Amylin-insulin Mixtures In Insulin-dependent Diabetes Mellitusmentioning
confidence: 97%